Implementation of Local Cultural Values in the Formation of Students' Morals at MA Al-Ma'arif Pinrang - Harmaen, Dheni (The International Journal of Education Management and Sociology, 2024)
This study aims to provide an accurate depiction of the relationship between the implementation of local cultural values and the development of students' morals at MA Al-Ma'arif Pinrang. Utilizing a descriptive qualitative approach, the research required direct fieldwork to observe and interview subjects. Data collection methods included observation, interviews, and documentation from relevant sources. The findings indicate a strong correlation between Mandar culture and the formation of students' morals at MA Al-Ma'arif Pinrang. In conclusion, the integration of local cultural values plays a crucial role in shaping students' morals, making its ongoing implementation within the school environment essential.